Analytical feasibility of a solvent‐assisted flavour evaporation method for aroma analyses in bread crumb. Issue 20 (27th September 2018) - Pico, Joana; Oduber, Fernanda; Gómez, Manuel; Bernal, José
Abstract: The analysis of bread aroma is essential in order to evaluate its quality as well as to improve it. The use of different methodologies for the analysis of volatile compounds lead to varying results. In the present study, the matrix effect, extraction efficiency, limits of detection and quantification as well as the precision of a proposed solvent‐assisted flavour evaporation methodology were evaluated for the first time and compared with a reference method, both differing in the distillation step. The repeatability (<8%) and matrix effect (present in 15 of the 31 compounds) were improved with the proposed method but the extraction efficiencies (average of 52%) and the intermediate precision (>15%) were not as required. However, the applicability of the reference method was limited to breads with fat levels <2%. For breads higher in fat, the proposed method represents an alternative for aroma analysis.